Seedling VOCs induce host preference in Bagrada hilaris Burmeister - Arif M.A.; Guarino S.; Peri E.; Colazza S. (Research and innovation as tools for sustainable agriculture, food and nutrition security, 2020)
The Painted bug, Bagrada hilaris (Burmeister) (Hemiptera: Pentatomidae), is an invasive stink bug species native from Asia and Africa, recently reported in United States, Mexico and Chile. This pest attacks mainly cruciferous plants and results particularly aggressive to seedlings at cotyledon stage, causing severe tissue damage, and in some the death of the plant. In this study the role of VOCs emitted by seedlings of four cruciferous species in the host preference behaviour of B. hilaris was evaluated. Two choice experiments using the vertical open Y-shaped olfactometer were carried out testing the attraction of B. hilaris adults toward seedlings of Raphanus sativus, Eruca sativa, Brassica rapa and B. carinata. The VOCs emitted by seedlings of these species were also collected in headspace using solid phase micro-extraction (SPME) method and analyzed by gas chromatography mass spectrometry (GC-MS). The results of the behavioural experiment evidenced the B. hilaris preference for R. sativus, E. sativa and B. rapa over B. carinata. However, adults of B. hilaris did not elicit any significant preference among R. sativus, E. sativa and B. rapa. Results of the chemical analyses evidenced the VOCs of R. sativus, E. sativa and B. rapa have in common the same main compound identified as benzophenone, missing in B. carinata. These results suggest a role of this compound in the host preference elicited from B. hilaris and might be a possible candidate as attractant for this pest.
2. MEDFORUM 2018, 2018/09/18-20, Bari (Italy)